Factors explaining adolescents’ digital skills in Europe - Maria Symeonaki; Glykeria Stamatopoulou; Dimitris Parsanoglou (Humanities & Social Sciences Communications)
Abstract Information and Communication Technologies (ICTs) play a pivotal role in the everyday lives of children and adolescents, shaping their educational experiences, leisure pursuits, and well-being. Thus, it is imperative for young individuals to have the capacity to employ digital skills adeptly, leading to tangible advantages for their personal growth and development. Yet, despite being born and brought up in a digital era and surrounded by digital devices, children and young people may lack the necessary knowledge and digital skills essential for leveraging ICTs effectively and preparing for a life in a digital society. This challenge is closely linked to the concept of the digital divide, which highlights disparities in access to and effective use of digital technologies based on socio-economic and demographic factors. The present paper utilizes raw data from the latest PISA 2022 survey to examine factors explaining digital skill scores of 15-year-old students in Europe in connection with several socio-demographic variables, namely gender, parental education, and migration background, as well as interest toward ICT, distraction from digital devices, and time spent on the internet. The results reveal significant differences amongst countries, and potential predictors of digital skills are provided for each European country separately. Overall life satisfaction was also examined as a predictor of digital skills; however, it was excluded from the final model as a non-significant predictor. The findings carry significant implications for both research and policy, highlighting the necessity of targeted educational policies and interventions to mitigate digital disparities. Promoting balanced digital literacy development and fostering diverse, meaningful, and skill-oriented engagement with digital technologies across genders is essential to ensuring equitable digital opportunities for all students.